Da conscientização do sistema tributário nacional à construção da cidadania fiscal o desenvolvimento através do direito do consumidor à informação da carga tributária - Bezerra Júnior, Francisco Glauberto (2018)
The present work aims to highlight the transdisciplinary relationship between the complexity of the Tax System, Consumer Law and information on the tax burden, Fiscal Citizenship and Development as freedom. The complexity of the Brazilian Tax System brings obstacles to the freedom of the individual, depriving him of the necessary conscience to avoid the opulence and oppression of the Fiscal State. Once the consumer's right to be aware of the tax burden has been effective, fiscal transparency is promoted and the citizen has the possibility of becoming aware of the information necessary to combat this state of ignorance and becomes an active agent of changes in society, through the discussion of how much is passed on to the Fiscal State or in what way there is the return of the values collected for the society. At the moment, Fiscal Citizenship has to be raised, by promoting transparency, by expanding the real freedoms that people can enjoy, by eliminating barriers to material equality and, in the end, contributing to the Development process. For this purpose, the Fiscal State will be analyzed in the initial chapter, in the construction of the Brazilian Tax System, identifying the complexity of the tax burden and the need for fiscal transparency. As a result, the protection of the right to information in the Consumer Protection Code and its tax side, which is the right to information on the tax burden on consumption, will be dealt with, having as legal framework Law number 12.741/2012, which regulated the art. 150, § 5, of the Federal Constitution. Finally, a historical overview of Citizenship and its relationship with the acquisition of civil, political and social rights will be made, as well as how Citizenship was built in Brazil. It will be highlighted the importance of the right to information on the tax burden to the consumer as an awareness of the Brazilian Tax System for the formation of Fiscal Citizenship and how this transdisciplinary relationship promotes transparency for the individual and society and provides an environment conducive to the elimination of obstacles to development. The historical method and the hermeneutical method were used to elaborate the study, and as a methodological procedure the bibliographic research was added to a study of texts made available on the internet, jurisprudence, legislation, among others.